LAW OF “GOOD AND EVIL”, NON-LINEAR FUNCTION OF JUSTICE, POLITICAL REGIMES AND DEFORMATION OF POLITICAL SYSTEMS - S. G. Ol’kov (Russian Journal of Economics and Law)
Objective: to clarify the law of good and evil, the function (rule) of justice and to construct mathematical models of political regimes. Methods: 1) observation, analysis and synthesis; 2) deduction and induction; 3) using the laws of formal logic; 4) formal legal method; 5) mathematical modeling; 6) the study of mathematical functions; 7) differential calculus; 8) plotting. Results: the author has deduced: 1) the nonlinear law (function) of good and evil; 2) the non-linear function of justice; 3) the law (function) of political regimes. Scientific novelty: the author has calculated and found: 1) a nonlinear formula: D(Lcol) = -Lcol3, which represents the relationship between the acts of legal (public) relations subjects (D) and thecollective freedom (Lcol) - the law of "good and evil"; 2) a non-linear formula: Y(D) = D3, illustrating the relationship between the acts of legal relations subjects (D) and responsibility for their actions (Y) - a nonlinear function of justice; 3) a non-linear formula that shows the relationship between the individual (Lind) and collective freedom (Lcol) in the negative area of the function definition (collective negative freedom) and a formula reflecting the relationship between the individual and collective freedom in the positive area of the function definition (collective positive freedom); 4) has given a general classification of political regimes in the world describing their functions, showing the types of political systems deformation that occur due to the left-wise and right-wise shifts of collective freedom. Practical value: the possibility to use the obtained scientific results in the development of various legal theories.